2018
DOI: 10.1039/c7ee03031b
|View full text |Cite
|
Sign up to set email alerts
|

Graphene aerogels for efficient energy storage and conversion

Abstract: Concerns over air quality reduction and energy crisis resulting from rapid consumption of limited fossil fuels have driven the development of clean and renewable energy sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
233
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(248 citation statements)
references
References 257 publications
1
233
0
1
Order By: Relevance
“…candidates. [1][2][3] Meanwhile, the advanced electrochemical energy storage and conversion systems have showed a great significance in the high-efficiency utilization of these sustainable energy. [4][5][6] Owing to the low cost and rich abundance of sodium resource, the rechargeable Na-ion batteries have attracted more and more attention for large-scale stationary energy storage.…”
Section: Doi: 101002/aenm201903966mentioning
confidence: 99%
See 1 more Smart Citation
“…candidates. [1][2][3] Meanwhile, the advanced electrochemical energy storage and conversion systems have showed a great significance in the high-efficiency utilization of these sustainable energy. [4][5][6] Owing to the low cost and rich abundance of sodium resource, the rechargeable Na-ion batteries have attracted more and more attention for large-scale stationary energy storage.…”
Section: Doi: 101002/aenm201903966mentioning
confidence: 99%
“…With the rapid increases of energy demand and serious environmental issues caused by conventional fossil fuel, the renewable sustainable clean energy, such as wind, water, geothermal energy, has been widely regarded as most promising candidates . Meanwhile, the advanced electrochemical energy storage and conversion systems have showed a great significance in the high‐efficiency utilization of these sustainable energy .…”
mentioning
confidence: 99%
“…This result doesn't accord with the theoretical capacity of composite materials by thermodynamic calculation, but in accordance with other graphene aerogel assisted composites . It is concluded that the extra capacity is mainly originated from the high surface area of graphene aerogel which is favorable for Li‐ion storage . Consequently, contributions of graphene aerogel and iron oxide nanotubes to the capacity are both indispensable in the charging and discharging process.…”
Section: Resultsmentioning
confidence: 53%
“…There is a rather limited number of materials that can be prepared as aeromaterials, but this number is continuously increasing, especially for carbon‐based nanomaterials, such as carbon nanotubes, graphene, aerographite, etc . This tremendous development of aeromaterials is related to an impressive number of applications in energy storage and conversion (e.g., supercapacitors and solar cells), environmental protection (e.g., large absorption of crude oil, sensors), biological applications (e.g., drug delivery, tissue engineering, implantable devices, and biosensing) . An interesting application is electromagnetic shielding where ultra‐lightweight aeromaterials could replace the heavy metals used for this purpose in many industries, such as automotive and aerospace ones .…”
mentioning
confidence: 99%